صوارف التدبر في القرآن الكريم وسبل العلاج: دراسة موضوعية قرآنية - الدهشان، عبدالكريم حمدي خليل (عبدالفتاح محمود ادريس, 2019)
يهدف هذا البحث إلى بيان حد التدبر وصوارفه؛ ليكون جامعاً مانعاً، يشمل ألفاظه المقاربة والمقابلة، وذكر خلاصة استعمالات القرآن الكريم لهذا الموضوع، واللطائف المستفادة، وذكر أنواع صوارف التدبر في القرآن الكريم، وبيان سبل علاجه، وقد كان من نتائج هذا البحث أن صوارف تدبر القرآن الكريم متشعبة، ولكن أخطرها تلك الصوارف الناتجة عن سوء في المعتقد، ومن ثم شهوة شديدة، تجعل القارئ يلوي عنق النصوص؛ لتحقيق أهداف تتفق مع أهوائه، وضرورة أن يستفيد المتدبر من أصول وخطوات التدبر الأمثل لفهم القرآن الكريم، وأن جل الصوارف عن التدبر لها علاقة بالقلب، ويليها الجهل المعرفي، وقلة الاطلاع، وضعف الاستماع إلى العلماء والمتخصصين، وقد كان من أهم توصيات الدراسة تشجيع كافة المسلمين على اختلاف درجاتهم في العلم والإيمان، أن يتدبروا آيات القرآن الكريم، كل حسب طاقته وقدرته، وبما يتفق مع أصول التدبر.
The purpose of this research is to explain the extent of the study and its waviness to be inclusive, including all the words of the approach and the interview, and the summary of the uses of the Holy Quran for this subject, and the lessons learned, and the types of narrators in the Holy Quran, The Qur'an is intricate, but the most serious of these is the narratives resulting from bad faith, and hence lust, which makes the reader twist the neck of the texts to achieve goals consistent with his desires and the need for the trainee to benefit from the fundamentals and steps of the best understanding of the understanding of the Holy Quran. It has to do with the heart, and follow it The ignorance of knowledge and lack of knowledge and the weakness of listening to scientists and specialists. One of the most important recommendations of the study was to encourage all Muslims of all degrees in science and faith to master the verses of the Holy Quran, each according to his capacity and ability.
Keywords: علوم القرآن -- علم التفسير -- صوارف التدبر